Achievement Coaching at The Bola Vorjas Palembang Volleyball Club - Darista, Rinda; Murniviyanti, Liza; Imansyah, Farizal (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to examine the Achievement Coaching Process at the Vorjas Palembang volleyball club. The method used in this study is descriptive qualitative. The subjects of the study consisted of Administrators, Coaches, Athletes, and Parents of Athletes. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, presentation, and verification techniques. Data validity was obtained through data triangulation. The results of the study indicate that the Vorjas Palembang volleyball club focuses on Coaching Beginners, The organizational structure of the Vorjas Palembang club is well managed. The coach is nationally licensed. The training program is carried out in a disciplined manner six times a week, The club’s facilities and infrastructure are adequate. Club funding comes from monthly athlete contributions. Social support also comes from parents and families of athletes. The club’s Achievement Coaching is running well thanks to a clear organizational structure, effective funding management, and competent coaches.